2013
DOI: 10.1002/dys.1459
|View full text |Cite
|
Sign up to set email alerts
|

What Do Preservice Teachers from the USA and the UK Know about Dyslexia?

Abstract: The purpose of the study was to examine the knowledge base of preservice teachers from the USA and the UK of dyslexia as a language-based learning disability. A survey (both US and UK versions) was constructed using current research-based understandings of dyslexia as a language-based learning disability. One hundred and one preservice teachers from the USA and 70 preservice teachers from the UK were administered the survey. Results indicated that participants in the two groups demonstrated some similar accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
1
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(123 citation statements)
references
References 46 publications
9
88
1
10
Order By: Relevance
“…Therefore, nearly twice as many teachers mentioned visual factors than biological factors. This also supports findings from previous research that suggests teachers hold the understanding that dyslexia and visual functioning are related (Wadlington & Wadlington, 2005; Washburn et al, 2013). The current survey demonstrates that teachers mention visual issues when describing dyslexia, despite research being inconclusive about this relationship.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Therefore, nearly twice as many teachers mentioned visual factors than biological factors. This also supports findings from previous research that suggests teachers hold the understanding that dyslexia and visual functioning are related (Wadlington & Wadlington, 2005; Washburn et al, 2013). The current survey demonstrates that teachers mention visual issues when describing dyslexia, despite research being inconclusive about this relationship.…”
Section: Discussionsupporting
confidence: 88%
“…This supports findings from other research that has also shown that both the lay public and teachers use behavioural descriptors when thinking about dyslexia (Bell et al, 2011; Furnham, 2013; Mortimore, 2013; Washburn et al, 2013). It could be hypothesized that this is because teachers are more likely to witness the behavioural correlates of dyslexia in the classroom.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations